2018
DOI: 10.1029/2018gl077969
|View full text |Cite
|
Sign up to set email alerts
|

Energetic Electron Injections Deep Into the Inner Magnetosphere: A Result of the Subauroral Polarization Stream (SAPS) Potential Drop

Abstract: It has been reported that the dynamics of energetic (tens to hundreds of keV) electrons and ions is inconsistent with the theoretical picture in which the large-scale electric field is a superposition of corotation and convection electric fields. Combining one year of measurements by the Super Dual Auroral Radar Network, DMSP F-18, and the Van Allen Probes, we show that subauroral polarization streams (SAPSs) are observed when energetic electrons have penetrated below L = 4. Outside the plasmasphere in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 39 publications
1
40
0
Order By: Relevance
“…This polarization electric field leads to a strong E x B drift, which forms the fast westward drifting SAPS flow (Kunduri et al, 2017Landry & Anderson, 2018;Lejosne et al, 2018). During the growth phase, the R1/R2 currents progress equatorward as the polar cap expands.…”
Section: Discussionmentioning
confidence: 99%
“…This polarization electric field leads to a strong E x B drift, which forms the fast westward drifting SAPS flow (Kunduri et al, 2017Landry & Anderson, 2018;Lejosne et al, 2018). During the growth phase, the R1/R2 currents progress equatorward as the polar cap expands.…”
Section: Discussionmentioning
confidence: 99%
“…(These electrons have quite low magnetic moments compared to the electrons in the peak of the outer radiation belt.) For instance, Lejosne et al () showed some of the injections occurring deep into the inner magnetosphere could be due to a potential drop associated with subauroral polarization stream (SAPS) (e.g., Lejosne & Mozer, ). Are these electrons locally accelerated?…”
Section: Particle Acceleration and Transport In The Inner And Outer Zmentioning
confidence: 99%
“…SAPS flow variations are often connected to earthward plasma sheet flow bursts and the plasma pressure distribution in the ring current (e.g., Clausen et al, ; Ebihara et al, ; Gallardo‐Lacourt et al, ; Lyons et al, ). The development of SAPS is suggested to be associated with the injection of plasma sheet ions/electrons, which establishes the polarization electric fields (e.g., Califf et al, ; Garner et al, ; Lejosne et al, ; Makarevich & Dyson, ; Mishin et al, ; Yuan et al, ). It is also demonstrated that the SAPS electric field can erode the outer plasmasphere, which also correlates with the generation of storm enhanced density and plumes of elevated ionospheric total electron content (TEC) on the dayside (e.g., Foster et al, , ; ; Foster & Rideout, ).…”
Section: Introductionmentioning
confidence: 99%